Reactive Power: Optimal Dispatch with linear programming-PART A - Gómez-Ramírez, Gustavo Adolfo (2019)
The decision-making is based on technical, legal, but especially economic facts; it requires business experience in order to be successful and try to have the smallest impact as possible. In the following research part-A, it proposes an optimal dispatch of reactive power and to use linear programming. This power is relevant in the Electrical Power Systems for the voltage ́s control and regulation, and it contributes to the real power flow too. On the other hand, it is important to point out that the world’s power systems do not quantify their use nor establish prices; this research uses an easy tool, recommends a new rate ́s structures and in the future can be a way to reduce it. Finally, this work develops an IEEE-14 power system.